2011
DOI: 10.1007/s00894-011-1204-3
|View full text |Cite
|
Sign up to set email alerts
|

In silico quest for putative drug targets in Helicobacter pylori HPAG1: molecular modeling of candidate enzymes from lipopolysaccharide biosynthesis pathway

Abstract: Aimed at identification and structural characterization of novel putative therapeutic targets in H. pylori, the etiological agent of numerous gastrointestinal diseases including peptic ulcer and gastric cancer, the present study comprised of three phases. First, through subtractive analysis of metabolic pathways of Helicobacter pylori HPAG1 and human, as documented in the KEGG database, 11 pathogen-specific pathways were identified. Next, all proteins involved in these pathogen-specific pathways were scrutiniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…The importance of this step is to reduce unwanted cross reactivity of the drug and thus to inhibit its binding to the active sites of the homologous proteins in host (Sarkar et al, 2012). In in silico drug target identification method, the first step is considered as the filtration of homologous proteins to human proteome (Anishetty et al, 2005; Sarkar et al, 2012). This non-similarity analysis was carried out for the gut flora non-similarity proteins datasets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of this step is to reduce unwanted cross reactivity of the drug and thus to inhibit its binding to the active sites of the homologous proteins in host (Sarkar et al, 2012). In in silico drug target identification method, the first step is considered as the filtration of homologous proteins to human proteome (Anishetty et al, 2005; Sarkar et al, 2012). This non-similarity analysis was carried out for the gut flora non-similarity proteins datasets.…”
Section: Resultsmentioning
confidence: 99%
“…These types of proteins were considered as essential and it was clearly demonstrated that similar proteins which are crucial in one organism are likely to be essential in another. A potential drug target possesses a crucial feature for the existence of the pathogen and must be an indispensable protein (Sarkar et al, 2012). The 67 proteins (Drug Target, Data Sheet S6 and Figure 1) out of 721 non-homologous input proteins were nominated for the consecutive analysis and considered as vital for the existence of the pathogen as they have homologs with not more than the given threshold value (Supplementary Table, S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KDO8Ps is widely expressed in higher plants (Brabetz et al, 2000;Delmas et al, 2003); however, biochemical and structural investigations of the enzyme have largely been limited to bacteria (Woisetschlager and Hogenauer, 1987;Brabetz and Brade, 1997;Sarkar et al, 2012). The first evidence of a plant KDO8Ps was provided by the detection of Kdo-8-P synthase-like activities in eight different plant species, and from the partial purification of KdsA and its characterization in spinach (Doong et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this step is to define the non-homologous proteins of the pathogen as it's likely to prevent the cross-reactivity of drug compounds with the human host proteins [17]. 'Expect' value (e-value) fixed was <0.005 and a minimum bit score was> 100 to exclude the homologous sequences.…”
Section: Mining Of Suitable Proteinsmentioning
confidence: 99%